Quantitative Assessment of Left and Right Atrial Strains Using Cardiovascular Magnetic Resonance Based Tissue Tracking - Qu, Yang-Yang; Buckert, Dominik; Ma, Gen-Shan; Rasche, Volker (Frontiers in Cardiovascular Medicine, 2021)
Background: Left and right atrium (LA and RA) exert an essential and dynamic role in ventricular filling and hence affect heart performance. Strain quantification has been reported as a novel parameter to assess function. However, the assessment of bi-atrial strains with cardiovascular magnetic resonance (CMR) based techniques is still limited and gender- and age-specific normal values in a healthy population are missing. Methods: One hundred and fifty healthy volunteers (49.8 ± 17.3 years, 75 males) undergoing 1.5 Tesla CMR examination were retrospectively and consecutively recruited. LA and RA free wall (RAFW) radial and longitudinal strains (RS and LS) associated with atrial reservoir, conduit and booster pump functions were evaluated with CMR based tissue tracking (CMR-TT) technique. Results: The reservoir, conduit and pump LS resulted as 30.7 ± 10.2%, 19.5 ± 8.2%, 10.9 ± 3.7% for LA, and 52.2 ± 17.6%, 33.3 ± 14.2%, 19.1 ± 8.5% for RAFW, respectively. The amplitude of RA strains was significantly larger than that of LA strains, except for conduit RS. With the increase of age, the decrement of majority of reservoir and conduit strains were observed, while pump strains remained unaffected. Females presented with significantly larger RAFW strains compared with males, especially in the elderly. In addition to the positive correlation between atrial strains and emptying fraction, the negative correlation between atrial strains and volume index was also confirmed. Intra-observer reproducibility of LA strains was superior to RAFW strains (coefficient of variation: 10.12–17.04% vs. 10.80–27.36%, respectively), and the measurement of reservoir and conduit strains was more reproducible in comparison with pump strain. Conclusion: CMR-TT is a feasible and reproducible technique to quantify LA and RA strains and determine atrial phasic functions. The existence of age- and gender-related difference of strains suggests the necessity to establish specific normal values for individual populations.